Zones Virtopiques Die Virtualisierung der Heterotopien und eine mediale Dispositivanalyse am Beispiel des Medienkunstprojekts Zone*Interdite - Dander, Valentin (innsbruck university press, 2014)
How can Michel Foucault's notion of heterotopias be transposed into a concept that describes medial and, more specifically, virtual spaces? What could such virtualized heterotopias look like? Can we find traces of utopian thinking within them? Zones*Virtopiques answers these questions in two ways: first by constructing a conceptual framework using notions of utopia and heterotopia, as well as reality and virtuality; and second, by applying theoretical findings to Zone*Interdite, a media art project on military areas authored by Mathias Jud and Christoph Wachter. Therefore, a micro-analysis of medial dispositifs has been developed.